Competency Model for Allied Health Manager – An Interconnected Nature - Ka Hi Mak; Louise Kippist; Kathy Eljiz (Asia Pacific Journal of Health Management)
Objective: This paper presents management competencies required for Allied Health Managers (AHMs).